SCHOOLING OF TEACHING AND TEACHER TRAINING The socio-political context in the Instructionist Reform of the Sovereign State of Santander (1863-1870), preamble to the Normal Schools in Colombia - Acevedo Tarazona, Alvaro (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper describes and analyzes the political and social context that framed and led to the instructionist reform in 1870 in the Sovereign State of Santander, preamble of formal schooling of teaching and normal schools for the training of teachers in Colombia. It is proposed a local look that allows to place the circumstances that made possible and necessary to implement the reform in a specific region of Colombia during the second half of the XIX century. The text holds that in the Sovereign State of Santander between 1863 and 1870 there was an enabling political and social environment that favored the adoption of a radical reform of the public instruction system, and also that  the local elite identified  ideological elements and facts that justified intervention in the education sector. The text is divided into two parts: the first analyzes and describes the point of view of the ruling elite with respect to the public instruction, and the second describes the actual situation of the educational system that they wanted to reform. This work is a historical research based on primary sources which were cataloged and analyzed to obtain the data presented and it provides new insights into one of the most important educational reforms of the XIX century.